ANALISIS PENGGUNAAN APLIKASI DUOLINGO DALAM PENGUASAAN KOSAKATA SISWA SMP - Vidayanti; Firdaus, Masagus; Mayasari, Santi (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study investigates how junior high school students can improve their command of English vocabulary by using the Duolingo program. It tackles the problem of low vocabulary retention and student involvement that is frequently present in conventional language training. The purpose of the study is to find out how students view Duolingo as a gamified learning resource and what factors affect how well it helps them learn new words. A descriptive analysis approach was used, based on the results of several recent empirical investigations. The findings demonstrate how Duolingo greatly enhances students' learner autonomy, contextual usage, and vocabulary retention. More incentive and active engagement are encouraged by its gamified features, which include level progression, point systems, and rapid feedback. Compared to traditional techniques, students said using Duolingo to learn vocabulary felt more fun and less taxing. Additionally, the multimodal information on the platform accommodates different learning styles, and its adaptability promotes self-directed learning. However, other issues were also noted, like the need for teacher direction and digital inequality. The conversation focuses on Duolingo's contribution to raising student participation in class and encouraging proactive rather than passive behavior. In conclusion, Duolingo is a useful addition to vocabulary training in junior high EFL classes. It improves language learning results and encourages self-directed learning when carefully included into a blended learning framework. Its long-term effects and uses in many educational contexts are encouraged to be investigated in future studies.